2017
DOI: 10.1007/s10815-017-0933-3
|View full text |Cite
|
Sign up to set email alerts
|

The bovine embryo hatches from the zona pellucida through either the embryonic or abembryonic pole

Abstract: For the bovine embryo, there is nearly equal probability of hatching from the embryonic or abembryonic poles. Given that the surface area of the zona pellucida in contact with the TE overlying the ICM is less than for the remainder of the blastocyst, there is some preference for hatching through the embryonic pole. Thus, the bovine embryo is distinct from the mouse and human, where hatching occurs preferentially at the abembryonic pole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In humans, a previous study showed that fresh blastocysts usually hatch from the site opposite the ICM, although a few choose to hatch near the ICM or elsewhere 13 ; however, the correlation between hatching site and birth outcome was not evaluated. Conversely, another study employed fresh bovine embryos and showed that there was nearly an equal probability that hatching would occur ipsilateral or contralateral to the ICM 14 . Combined with our results on blastocyst hatching site inclination, we presume that different species have variable preferences in terms of blastocyst hatching site.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a previous study showed that fresh blastocysts usually hatch from the site opposite the ICM, although a few choose to hatch near the ICM or elsewhere 13 ; however, the correlation between hatching site and birth outcome was not evaluated. Conversely, another study employed fresh bovine embryos and showed that there was nearly an equal probability that hatching would occur ipsilateral or contralateral to the ICM 14 . Combined with our results on blastocyst hatching site inclination, we presume that different species have variable preferences in terms of blastocyst hatching site.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in humans, various authors have reported the formation of natural hatching sites close to the ICM [42,48] as well as opposite to the ICM [49,50]. For bovine embryos, nearly equal probability of hatching from the embryonic or abembryonic poles has been demonstrated [51]. However, while the issue of the possible influence of the AH site on the hatching rate, blastocyst implantation, and embryo development remains controversial [43,46,47] and requires further study, the proposed technique enables safe, quick, and reliable ZP drilling at both abembryonic and embryonic poles and thus seems to be very useful for improving the AH effectiveness and overall embryo development.…”
Section: Discussionmentioning
confidence: 92%
“…Cells that were TE were distinguished from cells in the ICM based on nuclear labeling for CDX2 using procedures similar to those previously published [4, 25, 44, 45]. The primary antibody was ready-to-use mouse monoclonal antibody against CDX2 (BioGenex, Fremont, CA, USA; reference AM392-5 M, lot AM3920917) For randomly-selected embryos, mouse 1gG (1 μg/mL) was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%